From Cabaret to International Festivals: The Accidental Cultivation of a Curatorial Approach. Issue 1 (1st March 2022) - Archer, Robyn
Abstract : I write not as an academic, but as a singer, writer of works for the stage, festival director, and arts advisor. The word curator first entered my understanding as the role of those working in art galleries and museums: those skilled individuals who "cared for" their collections. The word has now spread to many of the things that I do, including the way I have "put together" large international arts festivals.